Multi-omics profiling of cachexia-targeted tissues reveals a spatio-temporally coordinated response to cancer - Morigny, Pauline; Vondrackova, Michaela; Ji, Honglei; Brejchova, Kristyna; Krakovkova, Monika; Makris, Konstantinos; Trubacova, Radka; Samanci, Tuna F; Kaltenecker, Doris; Ng, Su-Ping; Karthikaisamy, Vignesh; Chrysostomou, Sophia E; et al. (Nature metabolism, 2026)
Cachexia is a wasting disorder associated with high morbidity and mortality in patients with cancer. Tumour-host interaction and maladaptive metabolic reprogramming are substantial, yet poorly understood, contributors to cachexia. Here we present a comprehensive overview of the spatio-temporal metabolic reprogramming during cachexia, using integrated metabolomics, RNA sequencing and 13C-glucose tracing data from multiple tissues and tumours of C26 tumour-bearing male mice at different disease stages. We identified one-carbon metabolism as a tissue-overarching pathway characteristic for metabolic wasting in mice and patients and linked to inflammation, glucose hypermetabolism and atrophy in muscle. The same metabolic rewiring also occurred in five additional mouse models, namely Panc02, 8025, ApcMin, LLC and KPP, and a humanised cachexia mouse model. Together, our study provides a molecular framework for understanding metabolic reprogramming and the multi-tissue metabolite-coordinated response during cancer cachexia progression, with one-carbon metabolism as a tissue-overarching mechanism linked to wasting.
Keywords: Cachexia; multiomika; lidé; myši; metabolomika; Mice; Metabolomics; Animals; Humans; Disease Models, Animal; zvířata; kosterní svaly; mužské pohlaví; modely nemocí na zvířatech; Glucose; Multiomics; Neoplasms; Male; Muscle, Skeletal; nádory; kachexie; glukosa